Analisis Finansial Budidaya Pembibitan Lele: Studi Kasus pada Kelompok Tani Unit Pembibitan Rakyat Mina Dalem Sari di Kota Denpasar - I Kadek Agus Bisena; I G.A.A. Ambarawati; Ni Wayan Sri Astiti (Universitas Udayana, 2015)
Demand for catfish consumption generally in Bali and especially in Denpasar is very high, therefore it must be brought from outside the island. The catfish farmers in Bali are still very short of catfish hatchery, where most of them are still brought from outside the island, especially from Java. This study aims to find out business feasibility for short term and long term horizon, as well as the competitive value of producing breeding catfish compared to buying them from Java. Location of the study was chosen by using purposive sampling method at UPR Mina Dalem Sari which is located in Peguyangan Kaja Denpasar. Methods of data collection were interviews, observation and documentation. The number of samples taken was using census of all 10 members of the group. Data were analyzed using analysis of the feasibility of short-term and long-term, as well as analysis of break even point. The results of the analysis for short-term investments show stable cash flow and gross margins were positive which indicates that the business is feasible to be run. Analysis of long-term business also shows that catfish hatchery in Denpasar is feasible to develop. It can be seen from the payback period on the fifth year and first month, NPV shows the positive value of Rp 237,800,470 and the IRR is 32.57%. With an average of 2,700,000 catfish hatchery production per year, this business is very profitable compared to inter-island trading from outside the island. This is indicated by the results of the break-even point of 373,911 hatchery / year. Catfish hatchery in Denpasar needs to be improved by doing more socialization to the society in order to maintain the market demands, and open employment. It is suggested to build the form of group